MANFAAT PENGGUNAAN MEDIA YOUTUBE TERHADAP PERKEMBANGAN ANAK SEKOLAH DASAR DI ASRAMA SPN CISARUA BANDUNG BARAT - Iqbal Rediansyah (Comm-Edu (Community Education Journal), 2020)
such as YouTube content that are popular with children namely online game tutorials, vloger content that is being hit on YouTube, see foreign music bands that are currently being hit are boy bands or girl bands from korea that is on the gadgets or computers respectively. This study aims to determine the process of managing YouTube media in knowledge and behavior towards children at an early age from 6 to 12 years. The theory used in this research is the PLS concept, Youtube. The researcher formulated The researcher formulated three questions 1. To find out the use of YouTube social media in early childhood in the SPN Cisarua Dormitory, 2. To find out the role of parents in managing YouTube's social media for children, 3. To see children's responses to the use of YouTube social media. YouTube media management in West Bandung Cisarua Dormitory in this study researchers used a quantitative approach. Data collected through interviews, observation and documentation. As for the population of this study yatu children who are housed in the Cisarua West Bandung Dormitory. The results of this study most children know about YouTube just for their pleasure and become their passion because every time they play more gadgets than playing outside.